POLA PENGELUARAN MAHASISWA KOST FAKULTAS EKONOMIKA DAN BISNIS UNIVERSITAS KATOLIK WIDYA MANDIRA KUPANG - Paulina S. Luruk; Equila D.E. Metom; Fransiska Y. Manbait (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the expenditure profile of students living in boarding houses based on survey data from 100 respondents. Data were collected through an online survey that included gender, study program, financial resources, average monthly expenses, rent, food/drink costs, college expenses, and factors influencing expenses. The results show that the majority of respondents are female (69%) and 98% rely on their parents as their primary financial source. Average total expenses are dominated by the range of IDR 1,000,000 - IDR 1,500,000 (42%). The largest expenditure is for food/drink (81% of respondents), and the price of basic necessities (74%) is the main factor influencing the amount of expenditure. Although the majority feel their pocket money is sufficient (77%), the high cost of basic necessities indicates financial pressure that needs to be managed well.Keywords: Expenditure Patterns, Prices, Basic Need.